2007
DOI: 10.1021/nl0630539
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Growth of Copper Sulfide Nanocrystals on Multiwalled Carbon Nanotubes and Their Application as Novel Solar Cell and Amperometric Glucose Sensor Materials

Abstract: Single-crystalline copper sulfide (beta-Cu2S) nanocrystals (NCs) were grown in situ on multiwalled carbon nanotubes (MWCNTs) by the solvothermal method. The morphology of the Cu2S NCs was varied from spherical particles (av size=4 nm) to triangular plates (av size=12 nm) by increasing the concentration of the precursors. The lattice matching between Cu2S and the MWCNTs would be an important factor in the growth of Cu2S NCs on the MWCNTs. The solar cells and the amperometric glucose sensors fabricated using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
205
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(221 citation statements)
references
References 46 publications
11
205
1
Order By: Relevance
“…Figure 13c,d shows SEM images of the motor, which consists of a plate attached to the outer SWNT of the DWNT, and various angular positions of the plate [177]. There is plenty of room, as well, for the application of few-walled carbon nanotubes in devices for energy harvesting/storage (solar cells, for example) and sensors [179][180][181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196][197]. Indeed, we currently feel that finally the synthesis methods have advanced significantly to be technologically useful for producing high quality materials that are appropriate for testing several CNT applications that have been proposed in the literature or have been poorly tested.…”
Section: Applications Involving Dwnts and Twntsmentioning
confidence: 99%
“…Figure 13c,d shows SEM images of the motor, which consists of a plate attached to the outer SWNT of the DWNT, and various angular positions of the plate [177]. There is plenty of room, as well, for the application of few-walled carbon nanotubes in devices for energy harvesting/storage (solar cells, for example) and sensors [179][180][181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196][197]. Indeed, we currently feel that finally the synthesis methods have advanced significantly to be technologically useful for producing high quality materials that are appropriate for testing several CNT applications that have been proposed in the literature or have been poorly tested.…”
Section: Applications Involving Dwnts and Twntsmentioning
confidence: 99%
“…Herein, we exploited the capacity of the ionic exchange reaction for forming multishelled structures and found that with proper manipulation of a precursor system and thus reaction kinetics, a series of anionic exchanges with a solid precursor can actually be conducted in a consecutive manner, which leads to formation of single-, double-, triple-, or even quadruple shells. More specifically, as shown in Figure 1, we will use a hybrid of cuprous oxide (cuprites, a p-type metal oxide [22][23][24] ) and poly(vinylpyrrolidone) (PVP) as a precursor solid to establish some general principles in controlling ionic exchange and the hollowing process for fabrication of complex multishelled Cu 2 S (chalcocite [25][26][27] ) hollow spheres. The colloidal Cu 2 O spheres ( Figure 1, step 1) were synthesized with a PVP-assisted polyol method (Supporting Information, Section S1), and the product arising from this process was mesocrystalline in nature, in which the Cu 2 O crystallites are actually incorporated with PVP, giving rise to a form of inorganic-organic hybrids.…”
mentioning
confidence: 99%
“…1,2 Glucose biosensor is increasingly being studied because of its importance to monitor blood glucose for treatment of both diabetics and nondiabetics. [2][3][4] Conducting polymers, 5 nanomaterials, 6-10 sol-gels, 2,11-15 etc. have been proposed for the immobilization of glucose oxidase.…”
mentioning
confidence: 99%